A feasibility study of an interactive shared single display groupware in resource constrained schools, Sarawak - Cheah, Wai Shiang; Mit, Edwin; Abdul Halin, Alfian (Education Development Center, 2016)
One pressing issue in resource constrained schools is the lack of access to computer facilities for learning. A single display groupware (SDG) is explored in this paper to provide an alternative solution for this limitation where it allows multiple users to work concurrently on a single computer display. This study aims to investigate the feasibility of SDG as an educational approach in resource constrained schools. The prototype SDG system RimbaIlmu, is designed and developed. Quantitative evaluations are carried out where the results indicate its feasibility in students’ engagement and learning performance, while overcoming technical constraints. Limitation of the SDG is also presented with the intent of guiding future improvements.